Cover Picture: A Versatile One‐Pot Access to Cyanoarenes from ortho‐ and para‐Quinones: Paving the Way for Cyanated Functional Materials (Chem. Eur. J. 15/2016). Issue 15 (10th March 2016) - Glöcklhofer, Florian; Lunzer, Markus; Stöger, Berthold; Fröhlich, Johannes
Abstract : Developing a new reaction is challenging ! The cover reflects the ups and downs experienced during the investigation of the novel synthesis of cyanoarenes from quinones, which is highlighted by the magnifying glass. The sometimes exhausting experiments were finally rewarded by the versatile new one‐pot reaction presented in the accompanying Full Paper. The significance for the field of materials chemistry is illustrated by the blueprint showing the crystal structure of 6, 13‐dicyanopentacene. More information can be found in the Full Paper by F. Glöcklhofer et al. onpage 5173 ff.